MITIGASI BANJIR BERDASARKAN HUJAN 3 HARIAN MAKSIMUM TAHUNAN DENGAN SIMULASI PEMASANGAN PARAPET DI KOTA SURAKARTA - Nurhidayati, Fridya Ikafitri; Hadiani, Rintis; Muttaqien, Adi Yusuf (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2023)
Surakarta City often floods when there is high rainfall, according to BNPB 2016 three consecutive days of rain can cause flood disasters. Hydrological analysis is needed to determine the flood discharge due to the maximum three-day rain. With the development of TRMM satellite rain data technology can be used in hydrological analysis to overcome the problem of limited data availability at rainfall gauges. The purpose of this research is to determine the value of discharge, inundation area caused by a maximum of three days of rain. In addition, this research also evaluates flood events and determines appropriate efforts in overcoming floodwater runoff by installing parapets. The use of HEC-RAS software in this research is for flood analysis and simulation of parapet installation in areas experiencing river water runoff. The calculated flood discharge is the annual flood discharge from 2000 - 2019. The method of calculating the discharge uses HSS Gama 1. Then flood tracing is carried out to determine the area of inundation that occurs. The process of mapping and determining the extent of flooding that occurred in each sub-district was carried out with the help of software GIS. The highest flood area due to river runoff occurs in Laweyan Subdistrict, which is 45,80 ha. From this location, a parapet installation simulation was carried out as one of the flood mitigation efforts. Simulation of parapet installation was carried out in Pajang Village and Laweyan Village, after simulating parapet installation, the flood area for Laweyan Subdistrict was 2,21 ha.